Affordable Housing and Cyclical Fluctuations: The Malaysian Property Market - Carmelo Ferlito (Institute for Democracy and Economic Affairs (IDEAS), 2018)
Economic reality shows us that business fluctuations are everywhere and the crisis that emerged in the Western world in 2007 is just the latest and most evident manifestation of such dynamics. As mentioned in Ferlito (2016a, pp. 202-203), which develops the vision brought out in Ferlito (2014a), capitalism without fluctuations does not exist. I expressed the idea that business cycles are unavoidable by developing the doctrine of the natural cycle (see in particular Ferlito 2016b, Chapter 3). I will now summarize that framework in order to describe the evolution of the property market in the last decade. Section 2 presents the theory of the natural cycle, which will be used in section 3 for the analysis of the Malaysian property market over the past decade. According to such framework, business cycles are originated from positive profit expectations and each expansionary wave is followed by a secondary wave, which can be called imitative-speculative, usually supported by credit expansion. Such an evolution can be observed in the Malaysian property market from 1997, while today the declining movement is already initiated. In section 4, I focus on certain disproportionalities in the housing industry, arguing that the investor focus on the high-end segment was not unjustified and that government action is crowding out private constructors from the affordable housing segment. In section 5, I present some free market-oriented policy suggestions, aiming to create the conditions to limit the insurgence of future crises, to face the coming property crisis, and to revive the affordable housing market. Section 6 concludes.
Keywords: E32; 330; Property market; Malaysia